WHEN THE FUTURE IS EMOTIONLESS: SILAS'S STORY AND HOW EMOTIONAL "DISEASE" CHANGED HIS LIFE IN THE FILM EQUALS (2015) - Cut Novita Srikandi; Dzikra Ashri Asyifa; Imas Pratiwi; Rani Kholidaziya; Syifa Maziyyatul Fikriyah (Globish: An English-Indonesian Journal for English, Education, and Culture, 2021)
The world assumes that someone who has emotions is someone who will harm themselves and those around them. Emotions that are considered as a disease called S.O.S. (switched of the syndrome). This research aims to analyze a film entitled Equals  (2015) that depicts a world with high technological advances and humans who do not have emotions. We will use the descriptive analysis method with Freud's psychoanalysis approach to analyze "Silas" as the main character who suddenly has an emotional feelings are forced to be hidden from the people around him including the woman he likes.There are three psychological structure of a person found in the psychology of literature that According to Sigmund Freud, namely the id, ego, and superego. The end result of this research we will see how Silas hides his feelings and find a solution about the situation. The story of Silas shows us about the emotional disease change his life in the future.